2005
DOI: 10.1111/j.1365-313x.2005.02584.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of cellulose‐enriched tension wood in Populus: global analysis of transcripts and metabolites identifies biochemical and developmental regulators in secondary wall biosynthesis

Abstract: SummaryStems and branches of angiosperm trees form tension wood (TW) when exposed to a gravitational stimulus. One of the main characteristics of TW, which distinguishes it from normal wood, is the formation of fibers with a thick inner gelatinous cell wall layer mainly composed of crystalline cellulose. Hence TW is enriched in cellulose, and deficient in lignin and hemicelluloses. An expressed sequence tag library made from TW-forming tissues in Populus tremula (L.) · tremuloides (Michx.) and data from transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
286
2
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 346 publications
(318 citation statements)
references
References 80 publications
(97 reference statements)
20
286
2
7
Order By: Relevance
“…In fact the plastidial pyruvate kinase has been involved in fatty acid synthesis in Arabidopsis seeds (Andre et al 2007;Baud et al 2007) and sucrose synthase is involved in oil accumulation, suggesting a coordination between glycolytic and fatty acid biosynthetic pathways (Troncoso-Ponce et al 2011). However, the upregulation of sucrose synthases in cork could also be a consequence of a higher demand of cell wall synthesis (Andersson-Gunnerås et al 2006;Wei et al 2015). In addition, we found several contigs showing significant homology with HXXXDmotif/BAHD acyltransferases and GDSL-like genes that are upregulated in cork oak outer bark (Table S6A) and although their role in the biosynthesis of suberin has not yet been described, they could also be relevant for the accumulation of this polyester according to the role of some members of these gene families (Girard et al 2012;Molina and Kosma 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In fact the plastidial pyruvate kinase has been involved in fatty acid synthesis in Arabidopsis seeds (Andre et al 2007;Baud et al 2007) and sucrose synthase is involved in oil accumulation, suggesting a coordination between glycolytic and fatty acid biosynthetic pathways (Troncoso-Ponce et al 2011). However, the upregulation of sucrose synthases in cork could also be a consequence of a higher demand of cell wall synthesis (Andersson-Gunnerås et al 2006;Wei et al 2015). In addition, we found several contigs showing significant homology with HXXXDmotif/BAHD acyltransferases and GDSL-like genes that are upregulated in cork oak outer bark (Table S6A) and although their role in the biosynthesis of suberin has not yet been described, they could also be relevant for the accumulation of this polyester according to the role of some members of these gene families (Girard et al 2012;Molina and Kosma 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the prevalence of neutral PMEs in active cells would allow cell wall expansion (Guglielmino et al 1996). Pectinesterase transcripts were among the differentially regulated and most strongly expressed genes in tension wood of Populus (Andersson-Gunneras et al 2006) and in the juvenile cambial region of E. grandis (Gallo De Carvalho et al 2008). A pectin methyl esterase from wood-forming tissues of hybrid aspen (P. tremula x tremuloides Michx.)…”
Section: Resultsmentioning
confidence: 99%
“…TW is formed on the upper side of the leaning stem, resulting in characteristic asymmetric growth, and it serves to correct the stem position (4). In addition to the striking increase in cambial cell divisions, TW has an altered anatomy, and the fibers form an additional inner, cellulose-rich, gelatinous secondary cell wall layer (G layer) (5).…”
mentioning
confidence: 99%